Arrhythmogenic Interaction Between Sympathetic Tone and Mechanical Stretch in Rat Pulmonary Vein Myocardium - Egorov, Yuriy V.; Rosenshtraukh, Leonid V.; Glukhov, Alexey V. (Frontiers in Physiology, 2020)
Rapid firing from pulmonary veins (PVs) frequently initiates atrial fibrillation which is a common comorbidity associated with hypertension, heart failure, and valvular disease, i.e. conditions that pathologically increase cardiomyocyte stretch. Autonomic tone plays a crucial role in PV arrhythmogenesis while its interplay with myocardial stretch remains uncertain. Two-microelectrode technique was used to characterize electrophysiological response of rat PV to adrenaline at baseline and under mild (150 mg of applied weight which corresponds to a pulmonary venous pressure of 1 mmHg) and moderate (10 g, 26 mmHg) stretch. Low adrenaline concentrations (25-100 nmol/L) depolarized the resting membrane potential selectively within distal PV (by 26+/-2 mV at baseline, 18+/-1 mV at 150 mg, P<0.001, and by 5.9+/-1.1 mV at 10 g, P<0.01) resulting in intra-PV conduction dissociation and rare episodes of spontaneous activity (arrhythmia index of 0.4+/-0.2, NS vs. no activity at baseline). In contrast, 1-10 umol/L of adrenaline recovered intra-PV propagation. While mild stretch did not affect PV electrophysiology at baseline, moderate stretch depolarized the resting potential within distal PV (-56+/-2 mV vs. -82+/-1 mV at baseline, P<0.01), facilitated the triggering of rapid PV firing by adrenaline (arrhythmia index: 4.4+/-0.2 vs. 1.3+/-0.4 in unstretched, P<0.001, and 1.7+/-0.8 in mildly stretched preparations, P<0.005, at 10 umol/L adrenaline) and induced frequent episodes of potentially arrhythmogenic atrial ‘echo’ extra beats. Our findings demonstrate complex interactions between the sympathetic tone and mechanical stretch in the development of arrhythmogenic activity within PVs that may impact an increased atrial fibrillation vulnerability in patients with elevated blood pressure.